O prvem obdobju delovanja Kustodiata za slovenske izseljence, zamejce, pripadnike narodnih manjšin in drugih etnij - Koprivec, Daša (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents the operation of the Department for the Slovene emigrants, the Slovene ethnic minorities in the neighbouring countries, and the members of the national minorities and other ethnicities at the Slovene Ethnographic Museum from its establishment in 1999 to the present. The article explains the reasons for the origin of the department and presents the activities of its curator in the fields of research, collecting material and exhibitions.
Keywords: Slovenski etnografski muzej; Ljubljana; kustodiati; izseljenci; zamejci; narodne manjšine; razstave; muzejske zbirke